2023
DOI: 10.3390/nu15061494
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Intestinal Homeostasis and NAD+ Biology in Regulating Incretin Production and Postprandial Glucose Metabolism

Abstract: The intestine has garnered attention as a target organ for developing new therapies for impaired glucose tolerance. The intestine, which produces incretin hormones, is the central regulator of glucose metabolism. Glucagon-like peptide-1 (GLP-1) production, which determines postprandial glucose levels, is regulated by intestinal homeostasis. Nicotinamide phosphoribosyltransferase (NAMPT)-mediated nicotinamide adenine dinucleotide (NAD+) biosynthesis in major metabolic organs such as the liver, adipose tissue, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 201 publications
(274 reference statements)
0
2
0
Order By: Relevance
“…Further supporting a role for SCD1 in the stimulus–secretion coupling chain in L cells, SCD1 inhibition was found to reduce the expression of genes related to glycolysis, as well as ATP and NADH production. These are processes that have previously been shown to affect L cell secretion [ 49 , 50 ]. In agreement, we found that Scd1 KD reduced the acute mitochondrial respiratory response as measured using the Seahorse assay.…”
Section: Discussionmentioning
confidence: 99%
“…Further supporting a role for SCD1 in the stimulus–secretion coupling chain in L cells, SCD1 inhibition was found to reduce the expression of genes related to glycolysis, as well as ATP and NADH production. These are processes that have previously been shown to affect L cell secretion [ 49 , 50 ]. In agreement, we found that Scd1 KD reduced the acute mitochondrial respiratory response as measured using the Seahorse assay.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal NAD+ biology plays an important role in intestinal homeostasis, and the administration of NMN, one of the NAD+ precursors, increases intestinal NAD+ biosynthesis and positively influences gut physiology in vivo [13] Furthermore, NAD+ precursors have been described as potent anti-inflammatory agents. In particular, intestinal inflammation may be rescued using NAD+-increasing approaches [9,14]. This beneficial effect may be elicited directly, as is the case with NA, through a direct interaction with the GPR109a receptor, which inhibits the immune activation of resident macrophages and protects against further inflammatory cell infiltration, or indirectly after their conversion into NAD+.…”
Section: Introductionmentioning
confidence: 99%